Professional C# 2012 and .Net 4.5 - Nagel, Christian, 1965- (Programmer to programmer., 2013)
The NET 4.0 was anothers major release of the product that also brought a new version and a huge new library for parallel programing. The NET 4.0 fremework is based on a update version of the 4.0 runtime with many outstanding new features.